1992
DOI: 10.1007/bf00006474
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic phosphate in exposed sediments of the River Garonne

Abstract: Fractionation of inorganic phosphates in sediments of the River Garonne was carried out during a period of low water discharge. Sediments were collected under 5 cm of water (LS), in the dried river bank (MS) and in the riparian forest (RS). Sediments were sampled at two dates, during a period in which the water level fell gradually, causing sediment LS to be air exposed.Sediments were analysed for total phosphate, iron bound phosphate (Fe(OOH)-P) using Ca-NTA and Ca bound phosphate (CaCO 3 P) using Na-EDTA.Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In the present study, however, P HCl was not influenced by pretreatment. Fabre (1992) and Kerr et al, (2010) also found the consistent result. However, less P HCl was extracted when anaerobic sediment was preserved in air for 89 days compared with that extracted from fresh sediment (Lukkari et al, 2007b Reduced sediment Long-term aerobic storage Increasing P BD strongly and decreasing P HCl Lukkari et al, 2007b Aerobic sediment Long-term anaerobic storage Decreasing P BD and P Org Lukkari et al, 2007b Aerobic sediment Long-term aerobic storage Decreasing P BD Lukkari et al, 2007b Surficial 2 cm sediment Nature and laboratory Increasing labile P and decreasing P Org ; Kerr et al, 2010 drying (desiccation) changes of P BD and P NaOH depending on the sediment characteristics; laboratory drying has no influence on P HCl and P Res N o n -c o m m e r c i a l u s e o n l y days, laboratory drying was finished in a short time, which might prevent changes in the P HCl content in the sediment.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the present study, however, P HCl was not influenced by pretreatment. Fabre (1992) and Kerr et al, (2010) also found the consistent result. However, less P HCl was extracted when anaerobic sediment was preserved in air for 89 days compared with that extracted from fresh sediment (Lukkari et al, 2007b Reduced sediment Long-term aerobic storage Increasing P BD strongly and decreasing P HCl Lukkari et al, 2007b Aerobic sediment Long-term anaerobic storage Decreasing P BD and P Org Lukkari et al, 2007b Aerobic sediment Long-term aerobic storage Decreasing P BD Lukkari et al, 2007b Surficial 2 cm sediment Nature and laboratory Increasing labile P and decreasing P Org ; Kerr et al, 2010 drying (desiccation) changes of P BD and P NaOH depending on the sediment characteristics; laboratory drying has no influence on P HCl and P Res N o n -c o m m e r c i a l u s e o n l y days, laboratory drying was finished in a short time, which might prevent changes in the P HCl content in the sediment.…”
Section: Discussionsupporting
confidence: 73%
“…o n l y Lukkari et al, 2007b). Drying has also been verified to increase P BD (Fabre, 1992;Kerr et al, 2010) (Tab. 5).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The storage of anaerobic sediment in aerobic condition has been verified to change P fractionation results, so does the storage of aerobic sediment in anaerobic condition Lukkari et al, 2007b). Golterman (1996) oxyhydroxides (Fabre, 1992;De Groot and Fabre, 1993;Kerr et al, 2010). In addition, drying decreases or has no influence on calcium bound P (De Groot and Fabre, 1993;Kerr et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Fabre (1992) found important differences in Tot-P concentrations and in fractional composition in sediment of the river Garonne (France). Fabre (1992) found important differences in Tot-P concentrations and in fractional composition in sediment of the river Garonne (France).…”
Section: Variability Of and Transfer Between P-fractionsmentioning
confidence: 99%